Aktivitas Sitotoksik Ekstrak Rimpang Temu Kunci (Kaempferia Pandurata) serta Pengaruhnya Terhadap Ekspresi Gen P53 dan Bcl-2 Pada Raji Cell Line - Peni Lestarini; Endang Astuti; Deni Pranowo (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
Abstract Cytotoxic activity of ethanol and n-heksana extract temu kunci (Kaempferia pandurata) rhizome and its effect to p53 and bcl-2 genes expression on Raji cell line had been carried out. The rhizome of K. pandurata was drained and extracted using ethanol and n-heksana as the solvent. The ethanol and n-heksana extract were tested to Raji cell line. The p53 and bcl-2 genes expression were observed by immunocytochemistry method. The result showed that ethanol and n-heksana extract from K. Pandurata had cytotoxic activity to Raji cell line. The IC50 values for ethanol and n-heksana extract were 4.87 μg / mL and 4.14 μg / mL. The ethanol and n-heksana extract from K. Pandurata extract had capability to increase p53 gene expression and decrease bcl-2 gene expression on Raji cell line. Keywords: Kaempferia pandurata rhizome , p53 dan bcl-2 gene expression, raji cell line